Fiqh Siyasah as an Analytical Framework for Literacy Policy Implementation: Evidence from West Lampung, Indonesia - Nurul Meydianti, Dinda; Marwin; Hendriyadi (Al-Adalah: Jurnal Hukum dan Politik Islam, 2026)
This article employs fiqh siyasah as an analytical framework to examine the implementation of regional literacy policies in Indonesia, using West Lampung Regency Regulation No. 13 of 2021 as a case study. The analysis focuses on the institutionalization of literacy governance and the qualitative dimensions of public participation. In response to debates within public policy literature regarding the gap between formalized legal provisions for participation and meaningful deliberative practices, this study adopts a qualitative juridical-empirical approach, repositioning fiqh siyasah from a normative framework into an empirical analytical instrument. The findings indicate that the implementation of literacy policy in West Lampung operates within a hybrid governance configuration, where formal legal mandates interact dynamically with community-based initiatives through the Regional Literacy Movement. Although public participation has been institutionalized and contributes to the legitimacy and sustainability of programs, the substantive influence of community actors in strategic decision-making remains limited. By operationalizing the principles of shura and maṣlaḥah as evaluative criteria, this article underscores the analytical capacity of fiqh siyasah to assess the quality of participation and the orientation of public interest in policy implementation.